Hubungan Kualitas Tidur Dengan Prestasi Belajar Murid Kelas X-Xii Di SMA Muhammadiyah 7 Yogyakarta - Istiqomah; Rachmawati,S; Rahmadewi,T (Infomasi dan Promosi Kesehatan, 2023)
Introduction: Learning achievement is a student's effort to achieve mastery of knowledge, abilities, habits and skills and attitudes after following the learning process which can be proven by test results. Learning achievement is very important in the world of education because it evaluates the achievement of changes in accordance with learning objectives or not. One of the factors that influence learning achievement is sleep quality. Purpose: This research aims to determine the relationship between sleep quality and the learning achievement of students in grades X-XII at SMA Muhammadiyah 7 Yogyakarta. Method: This research is quantitative research with correlation studies and cross-sectional data collection. The research subjects were 79 students in class X-XII at SMA Muhammadiyah 7 Yogyakarta with with a simple random sampling method. Data collection was measured using the PSQI questionnaire and documentation data on student learning achievement was analyzed using the Chi-Square test. Result: The research results showed that 58 respondents (73.4%) had good sleep quality and 21 respondents (26.6%) had poor sleep quality. It was found that 67 respondents (84.8%) had good learning achievements and 12 respondents (15.2%) had poor learning achievements. It was found that there was a significant relationship between sleep quality and the learning achievement of students in grades X-XII at SMA Muhammadiyah 7 Yogyakarta (p=0.000, r=0.703) Conclusions: Based on the research results, there is a significant relationship between sleep quality and the learning achievement of students in grades Therefore, students can maintain and improve sleep quality such as sleep duration and sleep start time.